Code Switching And Code Mixing In Classroom Interaction Among Fifth-Semester English Education Student - Sitinjak, Apriani Silviani; Pakpahan, Carolina; Saragi, Christina Natalina (Lembaga Riset dan Inovasi Almatani, 2026)
Code-switching and code-mixing frequently occur in bilingual or multilingual communities, including in classroom interactions. In the teaching and learning process, lecturers and students often switch or mix languages to make communication easier and more effective. This phenomenon is commonly found in English classes where both Indonesian and English are used during discussions. This research aims to identify the types of code-switching and code-mixing used in classroom interaction and to determine the most dominant type used by the lecturer and students. This study applied a descriptive qualitative method. The data were obtained through classroom observation of fifth semester students of the English Education Study Program. The researcher recorded the classroom interaction and transcribed the utterances containing code-switching and code-mixing. The total data found in this research were 80 utterances. The findings show that there are three types of code-switching and three types of code-mixing used in the classroom interaction. The types of code-switching include inter-sentential switching (4 data or 5%), intra-sentential switching (19 data or 23.75%), and tag switching (13 data or 16.25%). Meanwhile, the types of code-mixing consist of insertion (33 data or 41.25%), alternation (6 data or 7.5%), and congruent lexicalization (5 data or 6.25%). The most dominant type found in this study is insertion. In conclusion, code-switching and code-mixing play an important role in classroom communication. The lecturer and students use both languages to clarify explanations, express ideas more easily, and maintain interaction during the learning process.